Low willingness and patient–caregiver concordance regarding long-acting injectable antipsychotics in schizophrenia cases: a convergent mixed-methods study - Huaiming Zhang; Bo Wu; Jin Zhou; Pengnan Bai; Yiting Zhu; Yixuan He; Jia Hu; Qi Zhao; Chaowei Fu (Frontiers in Psychiatry, 2026)
Introduction Long-acting injectable antipsychotics (LAIAs) may improve treatment continuity in schizophrenia, yet their acceptance in community-based care remains limited. This study examined factors associated with willingness to use LAIAs and dyadic perceptions and barriers among patients with schizophrenia and their primary caregivers in Yangpu District, Shanghai, where LAIA services and financial support were available. Methods This convergent mixed-methods study included a paired questionnaire survey of 425 community-managed patients who met LAIA treatment criteria but had not used LAIAs and their primary caregivers. Semi-structured interviews were conducted with 32 patient–caregiver dyads until information saturation was reached. Quantitative and qualitative findings were integrated using a joint display. Results Willingness to use LAIAs was low among patients and caregivers (17.4% and 17.6%), and awareness was limited in both groups (26.6% and 28.0%). Four dyadic willingness profiles were identified: concordant unwillingness, patient-only willingness, caregiver-only willingness, and concordant willingness. Higher patient willingness was associated with female sex, patient LAIA awareness, physician recommendation at the highest frequency, and caregiver willingness, whereas higher caregiver willingness was associated with caregiver LAIA awareness, being married, and patient willingness. Qualitative findings explained low acceptance through safety and injection concerns, treatment inertia, limited knowledge, reliance on physicians, family-based decision-making, and service accessibility barriers. Discussion These findings suggest that supporting informed LAIA acceptance may require patient–caregiver-centered decision support, safety communication, and coordinated follow-up beyond service availability and cost support.